2019
DOI: 10.1002/jcla.23120
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of serum amyloid A and establishment of reference intervals in healthy adults

Abstract: Background: Serum amyloid A (SAA) plays a critical role in acute or chronic and is used in clinical laboratories as an indicator of inflammation. The elevated SAA is closely related to inflammation-mediated diseases, such as liver diseases, autoimmune diseases, metabolism-related diseases, amyloidosis, and tumors. However, there is no unified population reference interval for SAA. This study aimed to investigate the distribution of SAA in healthy Chinese adults 20-79 years of age and to establish its populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…However, there was a significant difference between SAA values in males and females, and between ages 15 and 39 and ≥ 40 years, suggesting that age and separate gender reference range may be used in future analysis. Contradict to the result of this study, Liu et al reported that the SAA levels were not notably different between gender and age [30]. This difference may have occurred because Liu only examined healthy populations.…”
Section: Figure 1: Roc Curve Analysis Of New Pulmonary Tuberculosis Diagnosiscontrasting
confidence: 57%
“…However, there was a significant difference between SAA values in males and females, and between ages 15 and 39 and ≥ 40 years, suggesting that age and separate gender reference range may be used in future analysis. Contradict to the result of this study, Liu et al reported that the SAA levels were not notably different between gender and age [30]. This difference may have occurred because Liu only examined healthy populations.…”
Section: Figure 1: Roc Curve Analysis Of New Pulmonary Tuberculosis Diagnosiscontrasting
confidence: 57%
“…Furthermore, the lack of association with disease duration suggests that the differences in SAA concentrations between RD patients and controls are likely to be manifest also in the early stages of the disease, potentially facilitating diagnosis and commencement of treatment. The reported associations between effect size and sex, indicating a relatively greater difference in SAA concentrations vs. controls in studies with a greater representation of male RD patients, represents an interesting finding as previous reports have shown similar SAA concentrations between males and females in healthy subjects [ 74 , 75 ], and in patients with cancer [ 76 ]. Similarly, the significant and negative association observed between the effect size of the between-group differences in SAA concentrations and body mass index is at odds with previous reports which highlighted positive associations between SAA, body mass index, and obesity in non-RD populations [ 77 , 78 ].…”
Section: Discussionmentioning
confidence: 52%
“…This was equally observed among copper-exposed and referent subjects and so may reflect a common component of smelter working conditions. All other median blood biomarker levels fell within the respective reported ranges (CRP: <0.2 to 10.5 mg/L, 46 IL-6: 1 to 13.1 pg/mL, 47 IL-8: 24.4 to 35.9 pg/mL, 42 tumor necrosis factor α: 7.91 to 12.73 pg/mL, 48 CC16: 14.4 ± 4.6 ng/mL, 49 ESel: 9.15 to 65.19 ng/mL, 44 NE: 123.5 ± 24.3 ng/mL, 50 and SAA: <11.0 μg/mL 51 ). However, there are limitations to comparing “healthy” subject value ranges between studies such as population demographics and experimental differences in the use of commercial analytical assays that hamper meaningful comparisons.…”
Section: Discussionmentioning
confidence: 99%